Support for the initial attachment, growth and differentiation of MG-63 cells: a comparison between nano-size hydroxyapatite and micro-size hydroxyapatite in composites - Filová, Elena (Dove Medical Press, 2014)
Hydroxyapatite (HA) is considered to be a bioactive material that favorably influences the adhesion, growth, and osteogenic differentiation of osteoblasts. To optimize the cell response on the hydroxyapatite composite, it is desirable to assess the optimum concentration and also the optimum particle size. The aim of our study was to prepare composite materials made of polydimethylsiloxane, polyamide, and nano-sized (N) or micro-sized (M) HA, with an HA content of 0%, 2%, 5%, 10%, 15%, 20%, 25% (v/v) (referred to as N0–N25 or M0–M25), and to evaluate them in vitro in cultures with human osteoblast-like MG-63 cells. For clinical applications, fast osseointegration of the implant into the bone is essential. We observed the greatest initial cell adhesion on composites M10 and N5. Nano-sized HA supported cell growth, especially during the first 3 days of culture. On composites with micro-size HA (2%–15%), MG-63 cells reached the highest densities on day 7. Samples M20 and M25, however, were toxic for MG-63 cells, although these composites supported the production of osteocalcin in these cells. On N2, a higher concentration of osteopontin was found in MG-63 cells. For biomedical applications, the concentration range of 5%–15% (v/v) nano-size or micro-size HA seems to be optimum.